DETERMINAN NIAT MELAKUKAN WHISTLEBLOWING DI KALANGAN MAHASISWA - Silooy, Revi Wilhelmina; Gainau, Paskanova Christi; Heder, Gieanto (Jurnal Akuntansi, 2023)
This research aims to examine the influence of attitudes, subjective norms and Machiavellian traits on the intention to carry out whistleblowing among students. The population in this study were all students majoring in Accounting. The sampling technique is purposive sampling. Data was obtained from distributing questionnaires online and analyzed using multiple linear regression. The results of this research show that attitudes influence accounting students' intention to whistleblowing, while subjective norms and Machiavellian traits do not have a significant influence on whistleblowing intentions